Conditions of prescription of anti-TNF agents in newly treated patients with inflammatory bowel disease in France (2011–2013). Issue 6 (June 2016) - Blotière, Pierre-Olivier; Rudant, Jérémie; Barré, Amélie; Racine, Antoine; Weill, Alain; Peyrin-Biroulet, Laurent; Carbonnel, Franck; Alla, François
Abstract: Background: Tumour necrosis factor inhibitors (anti-TNFs) are active but expensive drugs that induce and maintain remission in patients with Crohn's disease (CD) and ulcerative colitis (UC). Aims: To assess the trends in anti-TNF prescription and the conditions of prescription of these drugs in patients with inflammatory bowel disease (IBD) in France. Methods: Incidence study of anti-TNF use was performed based on French medico-administrative databases (SNIIRAM/PMSI). IBD patients who initiated adalimumab or infliximab between 2011 and 2013 were selected. Results: The number of new anti-TNF users increased from 4571 to 5875 between 2011 and 2013 (+29%). More specifically, the number of patients not treated with immunosuppressants (IS) during the previous 12 months increased from 2100 to 3007 (+43%), among whom 379 patients in 2011 and 570 patients in 2013 started combination therapy (+50%). These trends were observed for both CD and UC. Patients who were naïve of IS were hospitalised more frequently than those treated with IS prior to anti-TNF therapy. Conclusion: This study shows a rapid increase in new prescriptions of anti-TNF for both CD and UC in France between 2011 and 2013. These results suggest a change in medical practices, with anti-TNF agents prescribed more often as first-line maintenance treatment.